Desenvolvimento de aplicativo para avaliação institucional colaborativa da saúde neonatal intensiva - Rocha, Hermano Alexandre Lima (2015)
Infant mortality showed important reduction in Brazil and in the world between 1990 and 2014, focusing mortality on neonatal deaths (50% of infant deaths, currently), which is less sensitive to the simplest direct interventions of child care. Brazil today has high neonatal mortality, unevenly divided between regions of the country. The main causes of neonatal mortality are preventable, and dependent on the access to and the quality of service provided in the inpatient delivery and to the neonate. There is evidence that it is more cost-effective to carry out interventions in regions with worst indicators and most in need. This work is justified by the priority of improving the quality of neonatal assistance for neonatal mortality reduction. The aim of this study is to reduce neonatal mortality, through the development of an evaluative tool dynamic comparative neonatal intensive care units, which identify the points that need to be improved. We used data from the RENOSPE study (Northeast of Perinatal Health Network), a prospective multicentric cohort of hospital based in the nine States of the Northeast region in the period from July to December 2007, comprising 5,148 live births. Initially, proportional hazards models were used to evaluate the association between the determining factors and survival of newborns, with the regressive model of Cox. After the identification of the determinants, multiple regressive models were made simple to Cox with these variables and the variable home institution of the case as the model factors and survival time as dependent. After analysis, comparison of variables representing the service provided in the units by means of control charts of type less average standard deviation and attributes. To the representative, application was created in the web for continued use by the institutions. Several factors were identified determinants of reducing neonatal survival, and among these various impacted by the institution. The control charts were relevant for signaling graphically important variables. The application is fully functional, hosted on the website www.renospeweb.org. It is concluded that this study provides an effective tool to managers of neonatal intensive care units, with the use of carefully selected variables, to improving the assistance provided to newborns.